Meningkatkan Hasil Belajar Siswa Kelas VIII-A SMP Negeri 27 Banjarmasin Dengan Menerapkan Model Pembelajaran Kooperatif - Aswad, Ana Nadzifatul; Jamal, M. Arifuddin; Mastuang, Mastuang (Berkala Ilmiah Pendidikan Fisika, 2015)
Student learning outcomes is still low, it is because the conditions of learning that took place during this done a teacher-centered. General research objective is to describe how the implementation of cooperative learningÂ  to improve student learning outcomes VIII-A classes on the subject of pressure and specific purpose of this study is to describe, (1) adherence to the RPP, (2) social skills of students, (3) the results of student learning. This study is a Class Action Research (CAR) conducted in three cycles and stiap cycle consisting of planning, taking action, observing, and reflecting. Research result; (1) adherence to the RPP in the first cycle of 96%, the second cycle of 97% and 98% for the third cycle, (2) social skills of students in the first cycle of 90,5%, in the second cycle of 92,75%, and the third cycle of 94.25%,(3) mastery learning outcomes of students in the classical style on the first cycle of 91,66%, the second cycle of 96,66%, and 96,67% for the third cycle. The conclusion shows that the cooperative learning model Investigation Group can improve student learning outcomes VIII-A classes on the subject of pressure.Â Â